Caecocolic intussusception associated with a caecal polyp and concurrent hepatocellular carcinoma in a cat. Issue 1 (April 2017) - Boland, Lara; Lindsay, Scott; Brunel, Laurencie; Podadera, Juan; Bennett, Peter
Case summary: A 17-year-old female neutered domestic shorthair cat presented for several days of reduced faecal volume and a rectal prolapse. Physical examination revealed a 2 cm rectal prolapse, hepatomegaly and a low body condition score of 3/9. Haematology and biochemistry revealed a mild non-regenerative anaemia (haematocrit 24.5%; reference interval [RI] 30.3–52.3%), a mild mature neutrophilia (16.21 × 10 9 /l; RI 1.48–10.29 × 10 9 /l) and a mild increase in alanine aminotransferase activity (222 IU/l; RI 12–130 IU/l). Abdominal radiographs identified hepatomegaly. The rectal prolapse was reduced under general anaesthesia. Abdominal ultrasound identified a caecocolic intussusception and a large hepatic mass. Thoracic radiographs were unremarkable. Hepatic fine-needle aspirate cytology revealed well-differentiated hepatocytes. A typhlectomy was performed and the quadrate liver lobe, with mass, was resected. Gross examination of the caecum identified a focal polyp; histopathology showed moderate plasmacytic–lymphocytic typhlitis and reactive mucosal-associated lymphoid tissue. The hepatic mass was diagnosed as a well-differentiated hepatocellular carcinoma. Six weeks postoperatively the cat had gained 0.5 kg, had an improved body condition score of 5/9 and resolution of clinical signs. The cat died acutely 1 year later from an unknown cause. Relevance and novel information: Caecocolic intussusception is rare in cats and uncommon in dogs. This is the third report in a cat and the first associated with a caecal polyp. As reported in dogs, the outcome following surgery was good. Hepatocellular carcinoma is a rarely reported feline neoplasm, which may have a good prognosis with surgical resection.